2014
DOI: 10.1097/aap.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioid Inhibition of Chronic Low-Back Pain Influences Degree of Back Pain Relief After Morphine Administration

Abstract: Background and Objectives Factors underlying differential responsiveness to opioid analgesic medications used in chronic pain management are poorly understood. We tested whether individual differences in endogenous opioid inhibition of chronic low back pain were associated with magnitude of acute reductions in back pain ratings following morphine administration. Methods In randomized, counterbalanced order over three sessions, 50 chronic low back pain patients received intravenous naloxone (8mg), morphine (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 22 publications
3
32
1
Order By: Relevance
“…Thus, individuals low in the tendency to express anger may benefit greatly from administration of morphine if their innate capacity to generate endogenous opioid analgesia is also low. The findings we reported 5,6 – that individuals with low endogenous opioid function exhibit high levels of morphine analgesic responses – may pertain most strongly to those low in anger-out. Thus, only individuals low in endogenous opioid function and anger expressiveness may benefit from supplementation of deficient endogenous opioid analgesia by use of exogenous opioid analgesics.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Thus, individuals low in the tendency to express anger may benefit greatly from administration of morphine if their innate capacity to generate endogenous opioid analgesia is also low. The findings we reported 5,6 – that individuals with low endogenous opioid function exhibit high levels of morphine analgesic responses – may pertain most strongly to those low in anger-out. Thus, only individuals low in endogenous opioid function and anger expressiveness may benefit from supplementation of deficient endogenous opioid analgesia by use of exogenous opioid analgesics.…”
Section: Discussionmentioning
confidence: 64%
“…First, the morphine response for both healthy controls and chronic pain participants who reported both high levels of anger-out and exhibited low endogenous opioid function was smaller than the morphine response for healthy controls and chronic pain participants who reported low high levels of anger-out and exhibited low endogenous opioid function. In previous work, 5,6 we showed that individuals with low endogenous opioid function exhibited high levels of morphine analgesic responses to both induced acute pain and spontaneous low back pain. We surmised that people with poor endogenous opioid function could compensate for their low endogenous analgesic capacity by supplementing deficient endogenous analgesia with exogenous opioids, like morphine.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations